Transition Experiences of Former Collegiate Women’s Soccer Athletes - DeFreese, J.D.; Weight, Erianne; DeCicco, Jamie; Nedimyer, Aliza; Kerr, Zachary; Carneiro, Kevin; Mihalik, Jason; Chandran, Avinash (Journal of Intercollegiate Sport, 2021)
Athlete transition from American collegiate sport participation, to non-sport careers or professional sport, has been a topic of contemporary sport science research but it is still not well understood, especially in female athlete populations. Informed by extant transition theory, the current study purpose was to describe the transition experiences of former women’s collegiate soccer athletes, including both positive and negative contributing factors. Using a deductive conceptual content analysis, results showcase both positive (i.e., social support, career goals, recreational sport play) and negative (i.e., lack of a team/support, lack of soccer/competition, lack of direction) contributors to the post-collegiate sport transition for female soccer athletes sampled. The importance of athletic identity and potential transition resources were identified. Specifically, participants endorsed career guidance, physical activity/exercise, mentorship programming, and mental health resources as potentially helpful to future athletes. Study findings expanded upon relevant transition theory and former female athlete research. Our study results may inform future research and program development efforts aimed at former female collegiate athletes from soccer and other sports.